Properties and optimal manufacturing conditions of chicken feathers thermoplastic biocomposites. (February 2015) - Colom, X; Rahalli, A; Cañavate, J; Carrillo, F
The aim of this study was the analysis and characterization of composites based on thermoplastics (ethylene vinyl acetate, polypropilene and high-density polyethylene) and chicken feathers. Several composite samples with a content of 20% v/v of chicken feathers have been studied to determine the optimal manufacturing conditions of temperature, mixing time, and mixing speed to achieve the best tensile properties. The results have shown that the addition of micronized chicken feather (20% v/v) to thermoplastic matrices increases stiffness and provides a more brittle behavior. Ethylene vinyl acetate matrix also shows an ability to participate in second-order intermolecular interactions with chicken feathers, providing better tensile properties (tensile strength and toughness) than polypropilene and high-density polyethylene. Optimal manufacturing conditions were found for a mixing time of around 5 min; a mixing speed of 50 r min −1 ; and temperature values of 160℃ in case of high-density polyethylene, 120℃ for ethylene vinyl acetate, and 170℃ for polypropilene. Fourier transform infrared spectroscopy, differential scanning calorimetry and scanning electron microscopy analysis have been performed in order to provide further understanding of the compatibility and microstructural features that support the tensile properties of the materials.